Certification of Ochratoxin A Reference Materials: Calibration Solutions OTAN-1 and OTAL-1 and a Mycotoxin-Contaminated Rye Flour MYCO-1. (3rd December 2019) - Bates, Jennifer; Bahadoor, Adilah; Cui, Yi; Meija, Juris; Windust, Anthony; Melanson, Jeremy E
Abstract: Background: Among the regulated mycotoxins that contaminate global food supplies, ochratoxin A is particularly harmful as a nephrotoxin and suspected carcinogen. Objective: To support global measurement comparability, certified calibration solutions for ochratoxin A and [ 13 C6 ]-ochratoxin A (OTAN-1 and OTAL-1, respectively) as well as a mycotoxin-contaminated rye flour certified reference material (CRM) known as MYCO-1 were developed. Methods: Quantitative proton NMR was used along with maleic acid as an external standard traceable to the Système international (SI) to measure the concentration of ochratoxin A and [ 13 C6 ]-ochratoxin A for the calibration solutions. OTAN-1 and OTAL-1 were then used as a pair in double isotope dilution MS to certify the mass fraction of ochratoxin A in MYCO-1. The natural ochratoxin A CRM served as the primary standard for traceable quantitation, while the synthetic [ 13 C6 ]-ochratoxin A CRM served as the internal standard. Results: The certified mass fraction of ochratoxin A or [ 13 C6 ]-ochratoxin A in the two mycotoxin calibration solution standards was established to be 11.03 ± 0.32 µg/g ( k = 2) for OTAN-1 and 4.89 ± 0.18 µg/g ( k = 2) for OTAL-1. The mass fraction of ochratoxin A in the rye flour standard MYCO-1 was certified at 4.05 ± 0.88 µg/kg ( k = 2). Conclusions: These CRMs will support regulatory testing as they can be used in the method development, validation, calibration, and QC analysis of ochratoxin A. Highlights: This report highlights the methods used to certify OTAN-1, OTAL-1, and MYCO-1 as well as the challenges associated with producing such materials, which can be applied to a wide variety of other CRMs.